(untitled) (Práxis Educativa, 2017)
Graham Welch, Professor at the UCL/Institute of Education, is well respected and known all around the world. His interests in the development of singing in children has shed light on the field of singing in Music Education. He has been a specialist consultant for Government departments and agencies in the UK, Italy, Sweden, USA, Ukraine, UAE, South Africa and Argentina on aspects of music, education and teacher education. Publications number approximately three hundred and fifty and embrace musical development and music education, teacher education, the psychology of music, singing and voice science, as well as music in special education and disability. People don’t know much about his experience as a music teacher in English schools at the beginning of his career, an important "detail" that really makes a difference and marks his peculiarity in the field. In this interview, conducted on 01/02/2016, he talks about his experiences and other problems related to Music Education. Graham Welch, professor do UCL/Institute of Education (Londres), é muito respeitado e conhecido em todo o mundo. Seu interesse pelo desenvolvimento do canto nas crianças tem lançado luz sobre a área do Canto na Educação Musical. Welch tem atuado como consultor especialista para departamentos e agências governamentais no Reino Unido, Itália, Suécia, Estados Unidos, Ucrânia, Emirados Árabes Unidos, África do Sul e Argentina, com foco em aspectos da Educação Musical e formação de professores. Possui mais de 350 publicações chega aproximadamente a trezentos e cinquenta e elas abarcam o desenvolvimento musical e a Educação Musical, a formação de professores, a Psicologia da Música, canto e a ciência da voz, bem como a música na Educação Especial. Pode-se considerar que as pessoas não conhecem muito sobre sua experiência como professor de música nas escolas inglesas no início de sua carreira, um “detalhe” que realmente faz diferença e marca sua peculiaridade na área. Nesta entrevista, realizada em 01/02/2016, ele fala sobre suas experiências e outros problemas relacionados à Educação Musical.